Does more detailed information mean better performance? An experiment in information explicitness. (4th November 2014) - Shang, Zilu; Brooks, Chris; McCloy, Rachel
Abstract : Purpose: – Investors are now able to analyse more noise-free news to inform their trading decisions than ever before. Their expectation that more information means better performance is not supported by previous psychological experiments which argue that too much information actually impairs performance. The purpose of this paper is to examine whether the degree of information explicitness improves stock market performance. Design/methodology/approach: – An experiment is conducted in a computer laboratory to examine a trading simulation manipulated from a real market-shock. Participants' performance efficiency and effectiveness are measured separately. Findings: – The results indicate that the explicitness of information neither improves nor impairs participants' performance effectiveness from the perspectives of returns, share and cash positions, and trading volumes. However, participants' performance efficiency is significantly affected by information explicitness. Originality/value: – The novel approach and findings of this research add to the knowledge of the impact of information explicitness on the quality of decision making in a financial market environment.